Construction of Two Alternative Polyadenylation Signatures to Predict the Prognosis of Sarcoma Patients - Hu, Chuan; Liu, Chuan; Li, Jianyi; Yu, Tengbo; Dong, Jun; Chen, Bo; Du, Yukun; Tang, Xiaojie; Xi, Yongming (Frontiers in Cell and Developmental Biology, 2021)
Backgroud: Increasing evidence indicates that alternative polyadenylation (APA) is associated with the prognosis of cancers. Methods: We obtained gene expression and APA profiles of 259 sarcoma patients from TCGA dataportal and TC3A database, respectively. The prognostic signatures, clinical nomograms, and regulatory networks were studied by integrated bioinformatics analyses. Then, the immune cell infiltration profile was obtained from the ImmuCellAI. The associations between APA-based signature and immune cells was studied. Results: A total of 61 and 38 APA events were identified as overall survival (OS)- and progress free-survival (PFS)-related biomarkers, respectively. Two signatures were generated. The area under the curves (AUC) values of OS signature were 0.900, 0.928, and 0.963 in 2-, 4-, and 6-years, respectively. And the AUC values of PFS signature at 2-, 4-, and 6-years were 0.826, 0.840, and 0.847, respectively. Overall and subgroup analyses indicated that high-risk patients had a worse prognosis than low-risk patients (all p values<0.05). In addition, immunomics analyses indicated that there are different patterns of immune cell infiltration between low- and high-risk patients. Furthermore, two clinical-APA nomograms were established and the C-indexes were 0.813 and 0.809 for OS nomogram and PFS nomogram, respectively. Finally, two APA regulatory networks were constructed. FIP1L1-VPS26B was identified as a key regulating relationship and validated in the pan-cancer analyses. Conclusion: In this study, we identified prognostic predictors based on APA events with high accuracy for risk stratification in sarcoma patients and uncovered interesting regulatory networks in sarcoma which could be underlying mechanisms. This study not only provides novel potential prognostic biomarkers but promote precision medicine and provide potential novel research interests for immunotherapy.